Discourse emblems - Karasik, V. I. (Cognition, Communication, Discourse, 2018)
This article focuses on discourse emblems employed for identifying the participants and the settings of communication. The discussed criteria for classifying such emblems include the sphere of communication, tonality, and reference. It is argued that discourse emblems signify the societal, professional, geographical and ideological background of the speaker.